Protein quality malnutrition - Manary, Mark J.; Wegner, Donna R.; Maleta, Kenneth (Frontiers in Nutrition, 2024)
Protein quality is a term used to describe a food or a diet with respect to its amino acid composition, protein digestibility and protein bioavailability. When these parameters are specified, either by direct measurement or estimation, the amino acids provided from the diet are compared to the amino acids required by a healthy individual, and an adequacy ratio or score is assigned. There are two protein quality scoring systems in general use, the protein digestibility-corrected amino acid score (PDCAAS) and the digestible indispensable amino acid score (DIAAS), neither of which account for the dietary source of the protein. When considering malnourished children, there are metabolic adaptations which reduce the endogenous availability of amino acids and increase the requirements for protein synthesis. Increased amino acid requirements are primarily driven by the presence of acute infection and the needs for tissue accretion. Two large clinical feeding trials conducted with moderately malnourished children in which dietary protein quality was carefully measured are reviewed. The findings suggest that the protein quality score per se does not predict weight gain or recovery in these children, and that consuming milk protein confers advantages when compared to vegetable source proteins.